2013
DOI: 10.1002/jmri.24177
|View full text |Cite
|
Sign up to set email alerts
|

1H‐MR spectroscopy characterization of the adipose tissue associated with colorectal tumor

Abstract: Looking at the lipid tissue around a lesion through (1) H-MRS can return important information regarding its genesis and development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…A solution that should be investigated consists in designing a specific shaped voxel (prism‐like voxel for example, as mentioned previously). Nevertheless, the preliminary quantification results obtained on these spectra are consistent with ex vivo analysis (study performed on humans).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…A solution that should be investigated consists in designing a specific shaped voxel (prism‐like voxel for example, as mentioned previously). Nevertheless, the preliminary quantification results obtained on these spectra are consistent with ex vivo analysis (study performed on humans).…”
Section: Discussionsupporting
confidence: 84%
“…In inflammatory conditions and cancer areas, this wrapping fat can be infiltrated by the progressive inflammatory or tumoral lesions . It was suggested in 2014 by Mosconi et al that lipid tissues surrounding colorectal tumors could allow a further insight in the characterization of colorectal tumors. This study focused on MUFAs near the tumors and showed that the concentration of these fatty acids was increased, whereas fat located further away did not show this trend.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AT and its FA content have also been related to tumor progression by Mosconi et al [76] , who analyzed VAT peri-tumoral fat composition in CRC patients at different tumor stages. The total content of MUFA in close proximity of, but not far from the tumor lesion, was found significantly increased in patients at higher tumor stage, especially stage IV.…”
Section: Adipose Tissue Inflammation Fatty Acid Profile and Colorectmentioning
confidence: 99%
“…17 The composition of fatty acids in periprostatic tissue is altered in patients with aggressive prostate cancers, 18 the characterization of adipose tissue in close proximity to colorectal tumors showed an alteration of monounsaturated fatty acids related to the stage of the tumor. 19 …”
Section: Introductionmentioning
confidence: 99%